2020
DOI: 10.3390/polym12020285
|View full text |Cite
|
Sign up to set email alerts
|

A Feasible Method Applied to One-Bath Process of Wool/Acrylic Blended Fabrics with Novel Heterocyclic Reactive Dyes and Application Properties of Dyed Textiles

Abstract: Reactive dyes containing cationic groups have great potentiality as novel dyes, which can be applicable to one-bath dyeing of wool/acrylic blended fabrics. In this work, four novel heterocyclic reactive dyes containing cationic groups were designed by using m-aminophenyltrimethylammonium salt or N-(2-aminoethyl) pyridinium chloride salt as cationic groups, N, N-diethyl-1,3-benzenediamine as a coupling component, 2-amino-6-methoxybenzothiazole, 2-aminobenzothiazole or 3-amino-5-nitrobenzoisothiazole as diazo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…This result also correlates with previous studies by refs , . The result indicated real fixation of the dye on fibers via the nucleophilic substitution reaction and covalent bonding with the cellulose through anchimeric assistance between dye molecules and hydroxyl groups in cellulose. , …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This result also correlates with previous studies by refs , . The result indicated real fixation of the dye on fibers via the nucleophilic substitution reaction and covalent bonding with the cellulose through anchimeric assistance between dye molecules and hydroxyl groups in cellulose. , …”
Section: Resultssupporting
confidence: 92%
“…The result indicated real fixation of the dye on fibers via the nucleophilic substitution reaction and covalent bonding with the cellulose through anchimeric assistance between dye molecules and hydroxyl groups in cellulose. 46,47 ■ CONCLUSIONS In summary, cellulose was successfully obtained from SCB using alkaline pretreatment, bleaching, and xylanase treatment. The FTIR spectroscopy, Raman spectroscopy, and WI studies confirmed the removal of noncellulosic materials (hemicellulose and lignin) during these processes.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…First, the bleached bamboo bundle is immersed in the dye bath for a period of time, so that the dye molecules penetrate into the fiber bundle, and then the alkali agent is added to the same dye bath to make the dichlorotriazine group, and the cellulose molecule undergo a nucleophilic substitution reaction under the action of −OH to form a dye-fiber covalent bond, which not only shortens the dyeing time but also reduces energy consumption and wastewater discharge. The dyeing rate of the fibers was analyzed by adjusting the dye concentration, dyeing promoter concentration, and fixing agent concentration . Dyeing bamboo fiber bundles (DDB) can be obtained from the pretreated decolored bamboo bundles (DB) after dyeing.…”
Section: Introductionmentioning
confidence: 99%
“…The dyeing rate of the fibers was analyzed by adjusting the dye concentration, dyeing promoter concentration, and fixing agent concentration. 25 Dyeing bamboo fiber bundles (DDB) can be obtained from the pretreated decolored bamboo bundles (DB) after dyeing. The dyeing rate of the fibers was analyzed by adjusting the dye concentration, dyeing promoter concentration, and fixing agent concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes in acid dyes are banned because of the risk of carcinogenesis [14,15]. In recent years, new colorants and dyeing methods have been developed [16,17].…”
Section: Introductionmentioning
confidence: 99%